Anterior Cervical Discectomy and Fusion (ACDF): Comparison Between Zero Profile Implants and Anterior Cervical Plate and Spacer - Alimi, Marjan (Cureus, 2016)
Introduction: Interposition grafts combined with anterior plating currently remain the gold standard for anterior cervical discectomy and fusion. The use of anterior plates increases fusion rates but may be associated with higher rates of postoperative dysphagia. The aim of the current study was to determine the clinical and radiological outcomes following anterior cervical discectomy and fusion (ACDF) using zero-profile anchored spacers versus standard interposition grafts with anterior plating. Methods: This was a retrospective case series. A total of 53 male and 51 female consecutive patients (164 total operated levels) who underwent ACDF between 2007 and 2011 were included. The mean clinical follow-up was 15.7 ± 1.2 (SEM) months for patients with zero-profile implants and 14.8 ± 2.1 months for patients with conventional ACDF with anterior plating. Patient demographics, operative details, clinical outcomes, complications, and radiographic imaging were reviewed. Dysphagia was determined using the Bazaz criteria. Results: Clinical outcome scores improved in both groups as measured by the modified Japanese Orthopedic Association and Nurick scores. Zero-profile constructs gave rise to significantly less prevertebral soft tissue swelling compared to constructs with anterior plates postoperatively (15.74 ± 0.52 as compared to 20.48 ± 0.85 mm, p < 0.001) and at the latest follow-up (10.88 ± 0.39 mm vs. 13.72 ± 0.67 mm, p < 0.001). There was a significant difference in the incidence of dysphagia at the latest follow-up (1.5% vs. 20%, p=0.001, zero-profile vs. anterior plate, respectively). Conclusion: Zero-profile implants lead to functional outcomes similar to standard anterior plate constructs. Avoiding the use of an anterior locking plate may decrease the risk of persistent postoperative dysphagia.